Enhancement of Fracture Toughness in carbonate doped Hydroxyapatite based nanocomposites: Rietveld analysis and Mechanical behaviour. (June 2023) - Bhatnagar, Dhruv; Gautam, Sanjeev; Batra, Hemant; Goyal, Navdeep
Abstract: Highly nanocrystalline carbonated hydroxyapatite (CHAp) is synthesized by hydrothermal technique with four different stoichiometric compositions for microstructural and mechanical analysis. HAp is one of the most biocompatible material and addition of carbonate ions lead to increase in fracture toughness highly required in biomedical applications. The structural properties and its purity as single phase is confirmed by X-ray diffraction. Lattice imperfections and structural defects is investigated using XRD pattern model simulation, i.e. Rietveld's analysis. The substitution of CO3 2− in HAp structure leads to a decrease in crystallinity which ultimately lessens crystallite size of sample as verified by XRD analysis. FE-SEM micrographs confirms the formation of nanorods with cuboidal morphology and porous structure of HAp and CHAp samples. The particle size distribution histogram validates the constant decrease in size due to carbonate addition. The mechanical testing of prepared samples revealed the increase in mechanical strength from 6.12 MPa to 11.52 MPa due to the addition of carbonate content, which leads to a rise in fracture toughness, a significant property of an implant material from 2.93 kN to 4.22 kN. The cumulative effect of CO3 2− substitution on HAp structure and mechanical properties has been generalized for the application as biomedical implant material or biomedical smart materials. Graphical abstract: Image 1 Highlights: Investigated the structural properties of Carbonated-Hydroxyapatite using Rietveld Analysis. Microstructural characterization and particle size distribution are discussed through FESEM images. Carbonate substitution in HAp matrix enhanced mechanical strength and fracture toughness. Outlined the scope of Carbonated-Hydroxyapatite biomaterial for biomedical implant application.